The clinical impact of using p16INK4a immunochemistry in cervical histopathology and cytology: An update of recent developments - Bergeron, Christine; Ronco, Guglielmo; Reuschenbach, Miriam; Wentzensen, Nicolas; Arbyn, Marc; Stoler, Mark; Knebel Doeberitz, Magnus von (International journal of cancer, 2015)
Cervical cancer screening test performance has been hampered by either lack of sensitivity of Pap cytology or lack of specificity of Human Papillomavirus (HPV) testing. This uncertainty can lead to unnecessary referral and treatment, which is disturbing for patients and increases costs for health care providers. The identification of p16INK4a as a marker for neoplastic transformation of cervical squamous epithelial cells by HPVs allows the identification of HPV-transformed cells in histopathology or cytopathology specimens. Diagnostic studies have demonstrated that the use of p16INK4a immunohistochemistry substantially improves the reproducibility and diagnostic accuracy of histopathologic diagnoses. p16INK4a cytology has substantially higher sensitivity for detection of cervical precancer in comparison to conventional Pap tests. Compared to HPV DNA tests, immunochemical detection of p16INK4a-stained cells demonstrates a significantly improved specificity with remarkably good sensitivity. About 15 years after the initial observation that p16INK4a is overexpressed in HPV-transformed cells we review the accumulated clinical evidence suggesting that p16INK4a can serve as a useful biomarker in the routine diagnostic work up of patients with HPV infections and associated lesions of the female anogenital tract.